Stillbirths in Cameroon: an analysis of the 1998-2011 demographic and health surveys - Adidja Amani; Jobert Richie Nansseu; Guy Ferdinand Ndeffo; Andreas Ateke Njoh; Fabrice Zobel Lekeumo Cheuyem; Paul Roger Libite; Athanase A. Ateba; Solange Ngo Bama; Martina Lukong Baye; Georges Nguefack-Tsague; Robinson Enow Mbu (BMC, 2022)
Abstract Background Many countries, including Cameroon, have found it challenging to estimate stillbirths, as there are limited available reports accurately. This analysis aimed to assess stillbirth rates and identify risk factors for stillbirth in Cameroon using successive Demographic and Health Survey data. Methods We conducted a cross-sectional analysis of data collected during the Demographic and Health Surveys of 1998, 2004, and 2011. Data were analyzed using SPSS 20.0. Logistic regressions were used to identify factors associated with stillbirth through odds ratios (ORs) at 95% confidence intervals (CI). Results were considered statistically significant at p-value less than 0.05. Results The crude stillbirth rate was 21.4 per 1,000 births in 2004 and 24 per 1,000 births in 2011, with respective standard errors of 1.8 and 1.3. The stillbirth rate increased with the mother's age (p < 0.001). The stillbirth rate reduction was prolonged between 1998 and 2011, with an annual reduction rate of 1.6%. The study observed that residing in rural areas, low socioeconomic status, and low level of education were risk factors associated with stillbirths. Conclusion Cameroon's stillbirth rate remains very high, with a slow reduction rate over the last 20 years. Although some efforts are ongoing, there is still a long way forward to bend the curve for stillbirths in Cameroon; supplementary strategies must be designed and implemented, especially among rural women, the poor, and the less educated.